Aarons.english Instagram Account as Vocabulary Teaching Media: Students' Perception - Annisa Fairus Rachmadani; Hertiki Hertiki (Reforma : Jurnal Pendidikan dan Pembelajaran, 2023)
Vocabulary is one of the essential aspects of learning English. The key to being able to read, write, and speak anything in English is having a diverse vocabulary. Instagram can be utilized as an alternative learning media to get students' interest in learning vocabulary. The study aims to explore students' perception of using Instagram Aarons.english as a media for learning vocabulary. This study was conducted at SMP PGRI 1 Buduran Sidoarjo used a qualitative case study approach. The data were taken from grade 9th students through interviews with six students, observation, and documentation. Thematic analysis is used to analyze the data in this study. The results of the study revealed that Aarons.english Instagram account is very influential for students. Students get many benefits when learning vocabulary using Aarons.english such as students become interested and also motivated to continue learning vocabulary because of Aarons.english's way of explaining material well and fun, easy to understand, and detailed. Apart from learning vocabulary, students also get other knowledge from these Aarons.english Instagram account in the form of students knowing various kinds of new vocabulary such as phrasal verbs, the second form of verbs, adverbs, and how to pronounce English words correctly.